2021
DOI: 10.1016/j.imr.2021.100778
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal injections for coronavirus disease 2019 (COVID-19): A narrative review

Abstract: Background The outbreak of Coronavirus disease 2019 (COVID-19) has caused more than 180 million infections and 3.9 million deaths. To date, emerging clinical evidence has shown the synergetic benefits of Chinese herbal injections in treating this contagious respiratory disease. This review aims to summarize and analyze the efficacy and safety of Chinese herbal injections in the therapy of COVID-19. Methods The literature from 3 electronic databases, PubMed, CNKI, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…TCMIs, composed of active substances from traditional Chinese medicines, have been widely used in clinical practice. With the increased application of TCMIs, the reported adverse drug reactions (ADRs), including acute allergic reactions, have been non-negligible in medication. Yet, the mechanism of how most TCMIs work or react with the human body remains unclear due to the complex components from natural materials including plants, animal products, and minerals. Among all the possible factors that cause ADRs, macromolecular components including protein remnants from plants and animals, especially that from plants, could be dangerous if injected into the human body. The prescribed method to examine protein in The Pharmacopeia of the People’s Republic of China at present is based on the precipitation reaction with sulfosalicylic acid or tannic acid.…”
Section: Resultsmentioning
confidence: 99%
“…TCMIs, composed of active substances from traditional Chinese medicines, have been widely used in clinical practice. With the increased application of TCMIs, the reported adverse drug reactions (ADRs), including acute allergic reactions, have been non-negligible in medication. Yet, the mechanism of how most TCMIs work or react with the human body remains unclear due to the complex components from natural materials including plants, animal products, and minerals. Among all the possible factors that cause ADRs, macromolecular components including protein remnants from plants and animals, especially that from plants, could be dangerous if injected into the human body. The prescribed method to examine protein in The Pharmacopeia of the People’s Republic of China at present is based on the precipitation reaction with sulfosalicylic acid or tannic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the availability of Shenmai injections for COVID-19 has been evaluated by molecular docking and network pharmacology. Data showed that 22 compounds and 16 targets were predicted in the Shenmai injection that was shared with COVID-19 [ 50 ] .…”
Section: Herbal Medicines Regulate the Immune System And May Contribu...mentioning
confidence: 99%
“…TCM is commonly used in China to treat a variety of diseases (R. J. Li, Dai, et al, 2021; T. Liu et al, 2021; Xiang et al, 2021; M. Zhang et al, 2022; Zhu et al, 2021). It mainly treats diseases according to the theory of balance between Yin and Yang, while H. pylori infection belongs to the category of “damp‐heat pathogenic Qi ” or “toxin comes from pathogenic bacteria” (R. J. Li, Dai, et al, 2021).…”
Section: Treatment Strategies For H Pylori Infectionmentioning
confidence: 99%